METHODS OF LEARNING ENGLISH IN PRIMARY GRADES - Norkobilov , Murod G‘ayrat o‘g‘li (Educational Research in Universal Sciences, 2023)
Children enter the school with positive (physically fit, diligent and energetic, enterprising) and negative (shy, capricious, stubborn, stubborn, talkative) individual characteristics. They also differ from each other in their exposure to external stimuli. For example, some students enjoy music, some enjoy colors, and some still live in the world of fairy tales in their imaginations.